Implementasi Strategi Pengembangan Bisnis Dengan Business Model Canvas - Sukarno, Bangkit Rambu; Ahsan, Muhamad (Jurnal Manajemen dan Inovasi (MANOVA), 2021)
This study aims to determine the mapping of existing business strategies and develop new business strategies into a business model canvas. The method used is descriptive qualitative. Data were collected through observation, documentation, and interview. The collected data were analyzed using SWOT analysis and the results were elaborated into nine elements of the Business Model Canvas. The results showed that the business strategy obtained from the Business Model Canvas mapping is good enough because each element supports each other to increase revenue. The practical implication is that several strategies must be improvised to increase revenue, including by developing key resources, increasing the cost structure for advertising, and persuading customers to become resellers as key partnerships, customer relationships, and channels.